2011
DOI: 10.4097/kjae.2011.60.6.428
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine does not produce vasocontraction on human isolated gastroepiploic artery

Abstract: BackgroundRecently, the addition of dexmedetomidine to sedation regimens after cardiac surgery had been reported and there is a possibility that dexmedetomidine can cause vasoconstriction. Vasopressin has been used as a prophylactic treatment for refractory vasodilatory shock during coronary artery bypass graft (CABG). Also, vasopressin may play an important role in initiating spasms at the graft artery. Here we evaluate the direct effect of dexmedetomidine on isolated human gastroepiploic arteries and the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Coughlan et al found that higher DEX resulted in constriction of canine distal coronary artery by activation of peripheral α2-AR [ 12 ]. Another study also showed that DEX dosage administered in higher than clinical usage (>1.25 ng/mL) caused contraction of isolated human gastroepiploic arterial rings, while 0.36–1.25 ng/mL of DEX did not enhance the vasoconstriction caused by vasopressin in isolated human gastroepiploic arteries [ 13 ]. Our study present results observed in isolated porcine coronary arteries were consistent with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Coughlan et al found that higher DEX resulted in constriction of canine distal coronary artery by activation of peripheral α2-AR [ 12 ]. Another study also showed that DEX dosage administered in higher than clinical usage (>1.25 ng/mL) caused contraction of isolated human gastroepiploic arterial rings, while 0.36–1.25 ng/mL of DEX did not enhance the vasoconstriction caused by vasopressin in isolated human gastroepiploic arteries [ 13 ]. Our study present results observed in isolated porcine coronary arteries were consistent with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Showed that endothelial NOS inhibition is required for the indication of DEX-induced vasoconstriction of arteries, yet venous constriction does not require such treatment [ 21 ]. Yildiz [ 18 ] and Won-Sung Kim et al [ 22 ] indicated that clinical doses of DEX could not induce vasoconstriction in the human internal mammary artery and gastroepiploic artery. These findings are contrary to those of previous clinical trials.…”
Section: Discussionmentioning
confidence: 99%